Metastatic poorly differentiated chordoma: the eyes do not see what the mind does not know - Omar I. Omar I.; Maxim Al Ashhab (University of São Paulo, 2019)
Chordoma is a rare tumor. It has unique clinical, pathological and immunohistochemical characteristics. Accurate diagnosis is essential as the tumor shows an aggressive clinical course and requires a multimodal therapeutic approach. A case with wide spread distant metastatic disease that was initially thought to represent metastatic thyroid carcinoma is presented. Appropriate clincopathologic correlation and the histologic findings raised the possibility of poorly differentiated chordoma. The diagnosis was confirmed by immunohistochemistry for INI-1 and Brachyury. The approach to the diagnosis emphasizing the clinical and pathologic findings of this case is discussed and reviewed in the context of the published literature.